2013
DOI: 10.1002/glia.22477
|View full text |Cite
|
Sign up to set email alerts
|

New functions of Müller cells

Abstract: Müller cells, the major type of glial cells in the retina, are responsible for the homeostatic and metabolic support of retinal neurons. By mediating transcellular ion, water, and bicarbonate transport, Müller cells control the composition of the extracellular space fluid. Müller cells provide trophic and anti-oxidative support of photoreceptors and neurons and regulate the tightness of the blood-retinal barrier. By the uptake of glutamate, Müller cells are more directly involved in the regulation of the synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
486
3
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 616 publications
(496 citation statements)
references
References 253 publications
(496 reference statements)
3
486
3
4
Order By: Relevance
“…[6][7][8] Reactive gliosis including hypertrophy, enlargement of soma, and proliferation are the most obvious pathological changes that occur in Mü ller cells during diabetes. 9,10 Moreover, increased VEGF expression in Mü ller cells under hyperglycemic conditions is one of the major contributors to pathological intraocular neovascularization.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Reactive gliosis including hypertrophy, enlargement of soma, and proliferation are the most obvious pathological changes that occur in Mü ller cells during diabetes. 9,10 Moreover, increased VEGF expression in Mü ller cells under hyperglycemic conditions is one of the major contributors to pathological intraocular neovascularization.…”
Section: Introductionmentioning
confidence: 99%
“…This 'inverted' retinal structure is expected to cause blurring of the image and reduction in the photon flux reaching the photoreceptors, thus reducing their sensitivity [6][7][8][9] . It has been recently reported that retinal Müller cells act as light guides serving to transfer light across the retina, from the vitreo-retinal border towards the photoreceptors [10][11][12] . However, the basic question remains: How does light propagation via Müller cells through the neuronal layers of the retina affect vision?…”
mentioning
confidence: 99%
“…Both astrocytes and Müller cells in the retina cover the blood vessels with their endfeet forming the BRB [30]. The Müller cells are specialized radial glial cells and span through the entire thickness of the retina.…”
Section: Syncytium Coupled Cellsmentioning
confidence: 99%